Analysis Of Work Motivation, Compensation And Work Discipline On Employee Performance With Job Satisfaction As An Intervening Variable - Safitri, Ananda Nur; Sumastuti, Efriyani; Setyorini, Noni (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The important role of employees in the furniture industry in Jepara cannot be ignored. They have a vital role in producing and producing high quality furniture products that Jepara is proud of. The role of the furniture industry in Jepara in the local economy is very important. Apart from providing employment for thousands of employees, this industry also has a positive impact on other sectors such as transportation, logistics and trade. The aim of this research is to examine and analyze work motivation, compensation and work discipline on employee performance through job satisfaction as an intervening variable. The population used in this research were employees in 7 furniture industries in Jepara. This research is a quantitative study with a sample of 98 employees in 7 furniture industries in Jepara who have worked for 1 year. This research uses the Structural Equation Model Partial Least Square (SEM-PLS) method with the SmartPLS application version 3.2.9 to analyze the data. Based on the research results, it was found that work motivation variables had an effect on satisfaction, compensation variables had no effect on job satisfaction, work discipline variables had an effect on job satisfaction, job satisfaction variables had no effect on employee performance, work motivation variables had no effect on employee performance, compensation variables had an effect on employee performance, the work discipline variable has no effect on employee performance, the work motivation variable has no effect on employee performance which is mediated by job satisfaction, the compensation variable has no effect on employee performance which is mediated by job satisfaction, that the work discipline variable has no effect on employee performance which is mediated by job satisfaction.